Development of the Weaving Industry through the Adoption of Higher Education Science and Technology - Wardani, Dewi Kusuma; Mulyanto, Mulyanto; Hariyani, Endang Sri; Murni, Endri Sintiana; Yunianti, Esterica; Ranu, Arif; Indira, Fransisca Rahcmawati (STKIP Singkawang, 2024)
Weaving Yoga Art Business Partners, located in Klaten, Central Java, face challenges in business development, namely the limited design of woven motifs and fashion product designs, as well as the lack of optimal promotional media. The objectives of this service are as follows: (1) developing woven motif designs and improving the quality of woven products (both lurik weaving, ikat weaving, dobby weaving, painted weaving, and batik weaving); (2) developing designs for woven clothing products; and (3) creating promotional media designs, both print and digital, to increase marketing or partner turnover. The activity approach is participatory, involving business partners in planning, production processes, products, and the evaluation of activity results. The methods applied include interviews, discussions, observations, practice, training, product trials, and limited or mass production. Product trials have been well achieved which is implemented by the creation of weaving products and promotional media. The results achieved from these activities are: the creation of ten digital weaving designs, five striated weaving product designs, five ikat weaving product designs, three dobby weaving product designs, three painted weaving product designs, two batik stamp weaving product designs, twenty-two weaving-based fashion product designs, one product catalog, one promotional video, four weaving production tutorial videos, and the Yoga Art website.